COMMUNITY PARTICIPATION IN THE IMPLEMENTATION OF EDUCATION - La ALI; Thamrin ABDULLAH (Journal of Education and Leadership in Education, 2019)
The study aims to describe the community participation in education. Research using qualitative methods, with a phenomenological approach. Subjects of research include: chairman of the foundation, headmaster, head of the panel madrasah, teachers, parents, donors, community leaders, religious leaders, education observers / NGOs, and education experts. The results showed: (1) Public participation in education form of financial and non financial; (2) Patterns of community participation in education there is a direct and representative; (3) Factors that affect the community participation in the provision of education for the culture of boading schools are different from boarding schools in general, the alumni are scattered in various professions, managerial capabilities foundation’s president modernize madrassas, status and position of a person, a strategic location, communication, economy, gender, age, old habitation, and the opportunity to participate; and (4) Impact of community participation in education is positive and negative.